INTERSPECIFIC INTERACTIONS AND PRODUCTIVITY OF LEUCAENA LEICOCEPHALA AND CLITORIA TERNATEA UNDER ARID LAND MIXED CROPPING - A. A. Elfeel; A. A. Bakhashwain; R. A. Abohassan (Journal of Animal and Plant Sciences, 2013)
Leucaena leicocephala - Clitoria ternatea intercropping under arid dry saline soils was carried out during the period 2010-2012. The aim was to test the effect of tree/ crop productivity and interactions. Crop parameters measured were; relative growth rate (RGR), forage yield, quality and stomatal conductance (gs). Where tree parameters are; height and diameter growth and increase per month. In addition to tree and crop leaf area index (LAI) and soil chemical properties. The study showed that intercropping resulted in reduced crop forage yield and RGR, compared to sole crop. While, protein and most of the minerals were higher and fiber was lower in intercropped forage. Tree growth was remarkably higher under intercropping compared to sole crop. Strong relationship between LAI with tree and crop productivity was observed. Higher values of LAI were associated with higher crop and tree growth. Crop gs was significantly higher in sole crop compared to intercrop, whereas lower gs values were observed in mixed plots with higher tree LAI. Soil organic matter was higher in mixed cropped plots associated with lower soil EC and Na and Higher N, K, Ca and Mg. The study concluded that the presence of Clitoria had beneficial effects on tree growth, where the trees had negative effects on crop forage productivity and RGR.
Keywords: LAI; stomatal conductance; intercropping; productivity